Plasmaspheresis, adverse effects and its horizons in Covid-19. - Mazo-Betancur, Lorena (2022)
Plasmapheresis is a therapeutic procedure that consists of the extraction of blood in order to subsequently carry out the separation of cellular components and plasma through different mechanisms or techniques that have been improved over time. The objective of this review was to describe and detail some of the adverse effects associated with the therapeutic use of filtration plasmapheresis in addition to its use in patients with COVID-19. For this, a series of searches were carried out in different databases available such as Scielo, ScienceDirect and PubMed to gather bibliographic sources with a medical-scientific basis on the subject in question and, according to what was found, plasmapheresis presents a low percentage of complications, in addition to certain benefits for a select group of patients infected by Covid-19, however, more evidence is still needed regarding the effectiveness in this group of patients.